The Hand Metaphor as a Projective Tool of Applied Psychologist - Borodulkina, Tetyana (East European Journal of Psycholinguistics, 2017)
Abstract. Metaphorical images are viewed as a good projective tool in the work of applied psychologist. The author describes the use of metaphor both as projective and therapeutic tool. The paper substantiates the reasons for using various metaphors in psychological practice. A special attention is drawn to understanding metaphor as a means of expression and designing of senses, including the existential senses. First, metaphoric associative cards (MAC) with images are introduced as the media of psychological practice. They employ the metaphor of ‘hand’ as an important projective material in the work of the practical psychologist. The author discusses the symbolic nature of ‘hand’ and scientific background of using this image in applied psychology as diagnostic method along with various metaphoric cards. Results of the study proved that the objective use of the ‘hand’ metaphor facilitates the applied psychologists to overcome patients’ psychological problems related to health, maturity and aging, sexual and parental relationships, social status. On the other hand, its symbolic application helps the psychologist find some solutions to the individual problems of power and subordination, violence and punishment, protection and posession, traumatic experience, stress coping and crisis overcoming strategies, mental health and ethical and moral existential issues.ReferencesAlbedil, M.F. (2013). “Ty derjish mir v prostertoi dlani”: simvolika ruki [«You hold the world in the stretched out arm»: arm’s symbolics]. Teoriia Mody, 27, 155–172. Retrieved from: http://www.nlobooks.ru/node/3296.Anastazi, A., & Urbina, S. (2001). Psikhologicheskoe Testirovanie [PsychologicalTtesting]. S.-Petersburg: Piter.Vachkov, I. V. (2006). Metaforicheskii Trening [Metaphorical Training]. Moscow: “Os-89”.Metaforicheskie assotsiativnue karty. Rukovodstvo k primeneniiu [The Metaphoric Cards. Guidance for the Use] Germany: OH Verlag. Retrieved from http://pushkov.com.ua/ohcards/item/53-instrukcii-k-katam.html. 6.Mikhina, І. М. (2003). Rozvytok tvorchykh zdibnostei doshkilnykiv zasobamy terapevtychnoi metafory [Development of creation in under school age children by means of therapeutic metaphors]: Extended Abstract of Ph.D. dissertation. Ivano-Frankivsk.Mylnikova, N.V. (2009). Struktura i funktsionirovanie kontsepta «ruka» v russkom yazyke [Structure and functioning concept «hand» in Russian]. Extended Abstract of Ph.D. dissertation. Samara.Mylnikova, N.V. (2009). Funktsionalnyi aspekt soderjaniia kontsepta «ruka» [Functional aspect of the maintenance concept «hand»]. Vestnik Samarskogo Gosudarstvennogo Universiteta, 67, 157–163. Retrieved from: http://cyberleninka.ru/article/n/funktsionalnyyaspekt-soderzhaniya-kontsepta-ruka.Ortega y Gasset, J. (1990). Dve velikie metafory [The two great metaphors]. In: Teoriya Metafory. (pp. 68–82), N. Arutyunova, M. Zhurinska, (Eds.). Moscow: Progress.Pezeshkian, N. (2001) Psikhoterapia Povsednevnoi Zhizni: Trening Razrecheniia Konfliktov [Psychotherapy of a Daily Life: Training to Resolve Conflicts]. S.-Petersburg: Rech.Pergamenshchik, L. A. (2015). Teoreticheskiie osnovaniia krizisnoi psikhologii [The theoretical basis of the crisis psychology]. Lichnost v Ekstremalnykh Usloviiakh i Krizisnykh Situatsiiakh Zhiznedeiatelnosti, 5, 92–100. Retrieved from http://elib.bspu.by/handle/doc/9116.Popova, A. R. (2004) Polisemant Ruka i realizatsiia ego leksiko-frazeobrazovatelnykh vozmojnostei v russkom yazyke [Polysemant Hand and realisation of its lexical and phraseological possibilities in Russian]. Extended Abstract of Ph.D. dissertation.. Orel.Popova, A.R. (2009). Frazeobrazovatelnyi potentsial polisemanticheskoi leksemy i ego realizatsiia v natsionalnom russkom yazuke (na primere sushchestvitelnogo ruka) [Phraseological potential polysemantic lexemes and its realisation in national Russian (on an example of a noun a hand) Vestnik Cheliabinskogo Gosudarstvennogo Pedagogicheskogo Universiteta, 5, 264–277 Retrieved from http://cyberleninka.ru/article/n/frazeoobrazovatelnyy-potentsial-polisemantichnoyleksemy-i-ego-realizatsiya-v-natsionalnom-russkom-yazyke-na-primere.Ruka (simvol) [Hand (symbol)]. Megaentsiklopediia Kirilla i Mefodiia. Retrieved from: http://megabook.ru/article/Рука%20(символ).Svirepo, O. А., Tumanova, O. S. (2004). Obraz, Simvol, Metafora v Sovremennoi Psikhoterapii [Image, Symbol, Metaphor in Modern Psychotherapy]. Moscow: Institute of Psychotherapy.Shragina, L. I. (2016). Psykhologiia Verbalnoyi Uiavy: Funktsionalno-Systemnyi Pidkhid [The Psychology of Verbal Imagination: The Functional and Systemic Approach]. Kyiv: Kyiv-Mohyla Academy Publishers.
Keywords: metaphor; metaphorical images; visual metaphor; Metaphoric Cards; the image of hand; the metaphor of hand; applied psychologist.